Preparation method of lithium manganese iron phosphate material, lithium manganese iron phosphate material and battery
By adding porous carbon in the preparation process of lithium manganese iron phosphate material and sintering it to form a three-dimensional conductive network, the problem of poor conductivity of lithium manganese iron phosphate material is solved and its electrochemical performance is significantly improved.
Patent Information
- Application Number
- CN202411679762.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
AI Technical Summary
Lithium manganese ferrophosphate material itself has poor electrical conductivity, which hinders its large-scale promotion and application in batteries.
By providing a mixed liquid, including a lithium source, an iron source, a manganese source, a phosphorus source, a porous carbon and a solvent, it is dried and crushed to obtain a first precursor and sintered under a protective atmosphere to form a lithium manganese iron phosphate material with a three-dimensional conductive network.
The conductivity and electrochemical properties of lithium manganese iron phosphate material have been significantly improved, and its application in batteries has been promoted.
Smart Images

Figure CN119660696A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a lithium iron manganese phosphate material, a lithium iron manganese phosphate material and a battery. Background Art
[0002] Lithium iron phosphate (LFP) is considered to be one of the promising cathode materials for lithium-ion batteries due to its advantages such as low price, abundant production and good cycle stability. However, since the operating voltage of lithium iron phosphate is only 3.2V, it cannot meet the requirements of high-energy power batteries, which limits its further development. In recent years, lithium manganese iron phosphate (LMFP) has attracted much attention in the market as an upgraded alternative material to lithium iron phosphate. Lithium manganese iron phosphate is a high-voltage phosphate material that is doped with a certain proportion of manganese on the basis of lithium iron phosphate, and the voltage platform of the material is increased by adjusting the manganese-iron ratio. Since lithium manganese iron phosphate combines the advantages of lithium iron phosphate and lithium manganese phosphate, it has attracted more and more attention. However, lithium manganese iron phosphate has an olivine structure similar to lithium iron phosphate, which leads to its poor conductivity, which seriously hinders its large-scale promotion and application in batteries. Summary of the invention
[0003] The embodiments of the present application provide a method for preparing a lithium iron manganese phosphate material, a lithium iron manganese phosphate material and a battery. The method for preparing the lithium iron manganese phosphate material can prepare a lithium iron manganese phosphate material with better conductive properties.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron manganese phosphate material, comprising:
[0005] Providing a mixed solution, the mixed solution comprising a lithium source, an iron source, a manganese source, a phosphorus source, porous carbon and a solvent;
[0006] Drying and crushing the mixed liquid to obtain a first precursor;
[0007] Under a protective atmosphere, the first precursor is subjected to a first sintering to obtain a lithium manganese iron phosphate material.
[0008] In some embodiments, in the mixed solution, the molar ratio of lithium, iron, manganese and phosphorus is (1.01-1.05):x:(1-x):1; wherein 0<x<1.
[0009] In some embodiments, the lithium source comprises lithium acetate;
[0010] and / or, the iron source comprises ferric acetate;
[0011] and / or, the manganese source comprises manganese acetate;
[0012] And / or, the phosphorus source comprises diammonium phosphate.
[0013] In some embodiments, the solid content of the mixed solution is 1%-10%.
[0014] In some embodiments, the mass ratio of porous carbon to manganese source is (1-10):100.
[0015] In some embodiments, a method for preparing porous carbon comprises:
[0016] Provide leaves;
[0017] The leaves are crushed, cleaned and dried to obtain pre-treated leaves;
[0018] The pretreated leaves are subjected to a second sintering and then ground into powder to obtain a second precursor;
[0019] adding the second precursor into an alkaline solution for ultrasonic treatment, and then drying to obtain a third precursor;
[0020] The third precursor is subjected to a third sintering process and then ground to obtain porous carbon.
[0021] In some embodiments, the pretreated leaves are subjected to a second sintering process, comprising:
[0022] The pretreated leaves are sintered at a temperature of 500°C-600°C for 1h-3h.
[0023] In some embodiments, adding the second precursor to an alkaline solution for ultrasonic treatment comprises:
[0024] The second precursor, the alkaline reagent and water are mixed in a mass ratio of 1:(3-8):16, and ultrasonically treated for 20-40 minutes; wherein the alkaline reagent includes at least one of lithium hydroxide and potassium hydroxide.
[0025] In some embodiments, subjecting the third precursor to a third sintering step comprises:
[0026] The third precursor is sintered at 800°C-900°C for 2h-4h.
[0027] In some embodiments, the mixed solution also includes a carbon source.
[0028] In some embodiments, the carbon source comprises glucose;
[0029] And / or, the mass ratio of the carbon source to the manganese source is (1-10):100.
[0030] In some embodiments, the mixed solution is dried and pulverized, comprising:
[0031] The mixture is freeze-dried at a temperature of -20°C to -50°C for 5h-8h and then ground into powder.
[0032] In some embodiments, performing a first sintering on the first precursor includes:
[0033] The first precursor is sintered at a temperature of 650° C.-900° C. for 7 h-12 h.
[0034] In a second aspect, an embodiment of the present application provides a lithium iron manganese phosphate material, which is obtained by the preparation method of the lithium iron manganese phosphate material as described above.
[0035] In a third aspect, an embodiment of the present application provides a battery comprising the lithium manganese iron phosphate material as described above.
[0036] Beneficial effects of the embodiments of the present application:
[0037] In an embodiment of the present application, a method for preparing lithium iron manganese phosphate comprises: providing a mixed solution, the mixed solution comprising a lithium source, an iron source, a manganese source, a phosphorus source, porous carbon and a solvent. Among them, the lithium source, the iron source, the manganese source and the carbon source can respectively provide lithium elements, iron elements, manganese elements and phosphorus elements for synthesizing lithium iron manganese phosphate. The porous carbon can adsorb lithium elements, iron elements, manganese elements and phosphorus elements into the porous structure of the porous carbon. After the mixed solution is dried and crushed, a first precursor is obtained. Under a protective atmosphere, the first precursor is sintered so that the lithium elements, iron elements, manganese elements and phosphorus elements adsorbed in the porous structure form lithium iron manganese phosphate, forming a lithium iron manganese phosphate material with a three-dimensional conductive network. That is, the method for preparing the lithium iron manganese phosphate material provided in the embodiment of the present application can prepare a lithium iron manganese phosphate material with a three-dimensional conductive network, thereby significantly improving the conductivity of the lithium iron manganese phosphate material and improving the electrochemical performance of the lithium iron manganese phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0039] Figure 1 3D structure diagram of lithium iron manganese phosphate material in the embodiment of the present application;
[0040] Figure 2 It is a comparison chart of the rate performance of lithium iron manganese phosphate materials in the examples of the present application and the comparative examples. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0042] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron manganese phosphate material, comprising:
[0043] Providing a mixed solution, the mixed solution comprising a lithium source, an iron source, a manganese source, a phosphorus source, porous carbon and a solvent;
[0044] Drying and crushing the mixed liquid to obtain a first precursor;
[0045] Under a protective atmosphere, the first precursor is subjected to a first sintering to obtain a lithium manganese iron phosphate material.
[0046] Among them, the lithium source, iron source, manganese source and phosphorus source can provide lithium, iron, manganese and phosphorus elements for the synthesis of lithium iron manganese phosphate material respectively. Porous carbon can make lithium, iron, manganese and phosphorus elements adsorbed into the porous structure. Then the mixed solution is dried and crushed to obtain a first precursor. Among them, the first precursor includes porous carbon and lithium, iron, manganese and phosphorus elements loaded on the porous carbon. The first precursor is first sintered under a protective atmosphere so that the lithium, iron, manganese and phosphorus elements form lithium iron manganese phosphate, and the lithium iron manganese phosphate is tightly combined with the porous carbon to obtain a lithium iron manganese phosphate material. In the lithium iron manganese phosphate material prepared in the embodiment of the present application, the porous carbon can serve as a conductive skeleton to form a three-dimensional conductive network, thereby significantly improving the conductive properties of the lithium iron manganese phosphate material, and can improve the electrochemical performance of the battery when applied to the battery.
[0047] In some embodiments, a mixed solution is provided, comprising:
[0048] Dispersing a lithium source, an iron source, a manganese source and a phosphorus source into a solvent to obtain a first mixed solution;
[0049] Porous carbon is added to the first mixed solution to obtain a second mixed solution.
[0050] Firstly, the lithium source, iron source, manganese source and phosphorus source are dispersed in the solvent to improve the uniformity of dispersion. Then, porous carbon is added to make the evenly dispersed lithium source, iron source, manganese source and phosphorus source be adsorbed into the porous structure, thereby improving the mixing efficiency and ensuring the utilization rate of the raw materials.
[0051] In some embodiments, in the mixed solution, the molar ratio of lithium, iron, manganese and phosphorus is (1.01-1.05):x:(1-x):1; wherein 0<x<1.
[0052] The molecular formula of lithium manganese iron phosphate is LiFe x Mn 1-x PO4, that is, when the amount of lithium element (Li) is 1 mol, the total amount of iron element (Fe) and manganese element (Mn) is also 1 mol. By making the ratio of the amount of each element satisfy the above conditions, the ratio of lithium element, iron element and manganese element in the first mixed solution meets the molecular formula requirements of lithium iron manganese phosphate, and then the regenerated lithium iron manganese phosphate material that meets the requirements is obtained through the reaction, which improves the utilization rate of lithium source and manganese source, reduces material waste, and saves costs. Increasing the proportion of lithium element helps to make the prepared lithium iron manganese phosphate material have more sufficient lithium ions to participate in the electrochemical reaction, reduce Li-Fe anti-site defects, improve the kinetic properties of lithium iron manganese phosphate materials, reduce the possibility of iron and manganese elements occupying lithium positions at high temperatures, and ensure the smooth flow of lithium ion diffusion channels.
[0053] It is understood that the ratio of the added lithium source and the manganese source can be reasonably adjusted according to the molecular formula of the desired lithium iron manganese phosphate material. For example, the value of x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.
[0054] In some embodiments, the lithium source includes lithium acetate (CH3COOLi). Lithium acetate has a low melting point and can be molten earlier in the sintering process, thereby providing a favorable liquid phase environment for the uniform distribution of the initial raw materials, increasing the contact area between the reactants, and helping to increase the reaction rate. In addition, lithium acetate releases a large amount of heat during the sintering process, which can provide the required energy for the nucleation of the lithium iron manganese phosphate material, promote crystal formation, and help to synthesize high-quality lithium iron manganese phosphate materials at a lower temperature.
[0055] In some embodiments, the iron source includes ferric acetate [Fe(OH)(CH3COO)2]. Ferric acetate has stable chemical properties, can provide the necessary iron element for the synthesis of lithium manganese iron phosphate material, and can be easily mixed with other raw materials to ensure the smooth progress of the reaction.
[0056] In some embodiments, the manganese source includes manganese acetate [Mn(CH3COO)2]. Manganese acetate can be used as a catalyst in the synthesis process to promote the synthesis of lithium manganese iron phosphate material. Manganese acetate can also control the growth rate of crystals and the morphology of the crystal structure, thereby improving the crystallization performance and electrochemical performance of the lithium manganese iron phosphate material. In addition, manganese acetate is a cheap material that can reduce the cost of lithium manganese iron phosphate material.
[0057] In some embodiments, the phosphorus source includes ammonium dihydrogen phosphate (NH4H2PO4). Ammonium dihydrogen phosphate has a high solubility in water, can be quickly dissolved in a limited time, and is adsorbed into the porous structure of the porous carbon. Ammonium dihydrogen phosphate has a high reactivity, can improve the efficiency of the reaction, and reduce the difficulty of the reaction. In addition, the cost of ammonium dihydrogen phosphate is low, which can reduce the cost of lithium manganese iron phosphate materials.
[0058] In some embodiments, the solid content in the mixed solution is 1%-10%. By setting the solid content in the mixed solution to, the dispersion performance of the lithium source, iron source, manganese source and phosphorus source in the first mixed solution can be ensured, so that the first mixed solution has a suitable viscosity.
[0059] In some embodiments, the mass ratio of porous carbon to manganese source is (1-10): 100. Porous carbon has a high specific surface area and excellent electrical conductivity, and can adsorb elements in lithium iron manganese phosphate in its porous structure, thereby compensating for the disadvantage of low electrical conductivity of lithium iron manganese phosphate. By setting the mass ratio of porous carbon to manganese source to (1-10): 100, the elements can be adsorbed into the porous structure of porous carbon to form a three-dimensional conductive network, and the gram capacity and energy density of lithium iron manganese phosphate material are guaranteed.
[0060] In some embodiments, a method for preparing porous carbon comprises:
[0061] Provide leaves;
[0062] The leaves are crushed, cleaned and dried to obtain pre-treated leaves;
[0063] The pretreated leaves are subjected to a second sintering and then ground into powder to obtain a second precursor;
[0064] adding the second precursor into an alkaline solution for ultrasonic treatment, and then drying to obtain a third precursor;
[0065] The third precursor is subjected to a third sintering process and then ground to obtain porous carbon.
[0066] That is, the porous carbon provided in the embodiment of the present application is obtained by sintering leaves. Leaves are widely available, low in cost, environmentally friendly and sustainable. The porous carbon prepared from leaves has a porous structure with a suitable pore size, can load lithium, iron, manganese and phosphorus, and form a good three-dimensional conductive network.
[0067] Specifically, the leaves can be ginkgo leaves, maple leaves and elm leaves. The pretreated leaves can be obtained by crushing, cleaning and drying the leaves. Among them, the leaves can be crushed by shearing, cutting, etc., the cleaning method can be ultrasonic cleaning, and the drying can be carried out at 80°C. The pretreated leaves are subjected to a second sintering to remove organic matter in the pretreated leaves and initially form a pore structure, and then ground into powder to form a second precursor. The second precursor is ultrasonically treated with alkali solution, and the non-carbon atoms (such as ash) and disordered carbon atoms in the second precursor are etched by alkali solution to optimize the pore structure and improve the purity. After drying, a third precursor is obtained. The third precursor undergoes a third sintering again to improve mechanical strength, enhance chemical stability, and evaporate the alkali solution adsorbed in the pores during the sintering process, expand the pore structure, and form porous carbon.
[0068] In some embodiments, the pretreated leaves are subjected to a second sintering process, comprising:
[0069] The pretreated leaves are sintered at a temperature of 500°C-600°C for 1h-3h.
[0070] Sintering the pretreated leaves at a temperature of 500℃-600℃ for 1h-3h can pyrolyze and burn most of the organic matter in the pretreated leaves, thereby removing these components that may interfere with subsequent treatments, and can also help to initially destroy the internal structure of the pretreated leaves to form pores.
[0071] In some embodiments, adding the second precursor to an alkaline solution for ultrasonic treatment comprises:
[0072] The second precursor, the alkaline reagent and water are mixed in a mass ratio of 1:(3-8):16, and ultrasonically treated for 20-40 minutes; wherein the alkaline reagent includes at least one of lithium hydroxide and potassium hydroxide.
[0073] By mixing the second precursor, alkaline reagent and water in the above proportion, the uniformity of the mixture can be ensured, and the alkaline reagent can act on the pores of the second precursor, thereby improving the reaction efficiency and optimizing the pore structure in the second precursor. Ultrasonic treatment can further ensure the mixing efficiency and allow the alkaline reagent to interact with the second precursor, and the chemical stability and mechanical strength can be improved after ultrasonic treatment.
[0074] In some embodiments, subjecting the third precursor to a third sintering step comprises:
[0075] The third precursor is sintered at 800°C-900°C for 2h-4h.
[0076] By sintering the third precursor at a temperature of 800-900°C for 2-4 hours, the pore structure can be further optimized, a stable pore structure can be formed, and the specific surface area and adsorption performance of the porous carbon can be improved. High-temperature sintering can enhance the mechanical strength of porous carbon and improve chemical stability. At the same time, during the high-temperature sintering process, the potassium or lithium elements adsorbed in the pores can form steam, which further catalytically activates the pores of the third precursor, thereby expanding the pore structure and allowing the porous carbon to form pores of suitable pore sizes.
[0077] In some embodiments, the mixed solution also includes a carbon source. By adding porous carbon to the mixed solution, the lithium, iron, manganese and phosphorus elements in the mixed solution can be adsorbed into the porous structure of the porous carbon, which helps to form a three-dimensional conductive network structure. The addition of a carbon source can coat the lithium iron manganese phosphate material through subsequent steps to form a coating layer, which can further improve the conductivity and build a more stable conductive network. The carbon coating layer can also provide protection for the lithium iron manganese phosphate material and improve the structural stability.
[0078] In some embodiments, the carbon source includes glucose. When glucose is carbonized and decomposed at high temperature, it can form a dense carbon network, which is tightly wrapped on the surface of the lithium manganese iron phosphate material to construct a conductive network and improve electronic conductivity. Glucose as a carbon source can improve the uniformity of the coating, provide a stable chemical and electrochemical reaction interface, and inhibit the dissolution of elements such as manganese. In addition, glucose has a wide range of sources and low cost, which helps to reduce costs.
[0079] In addition, carbon sources can also be sucrose, amino acids, starch, cellulose, etc.
[0080] In some embodiments, the mass ratio of the carbon source to the manganese source is (1-10): 100. By controlling the mass ratio of the carbon source to the manganese source within the above range, it is possible to ensure that the carbon source forms a conductive network after sintering and improve the structural stability of the formed coating layer. Reasonable ratios also help to improve energy density and reduce cost investment while ensuring safety.
[0081] In some embodiments, the mixed solution is dried and pulverized, comprising:
[0082] The mixture is freeze-dried at a temperature of -20°C to -50°C for 5h-8h and then ground into powder.
[0083] Freeze drying can maintain the chemical composition and physical properties of each component in the mixed solution to the greatest extent, which is helpful to form a stable lithium manganese iron phosphate material through subsequent sintering.
[0084] Illustratively, the freeze-drying temperature may be set to -20°C, -25°C, -30°C, -35°C, -40°C, -45°C, or -50°C.
[0085] In some embodiments, performing a first sintering on the first precursor includes:
[0086] The first precursor is sintered at a temperature of 650° C.-900° C. for 7 h-12 h.
[0087] By setting the sintering temperature to 650℃-900℃, the lithium, iron, manganese and phosphorus elements adsorbed in the porous carbon can form lithium iron manganese phosphate, and the carbon source can be fully carbonized, and the formed lithium iron manganese phosphate particles can be coated to form a coating layer. In this temperature range, lithium iron manganese phosphate can be tightly combined in the porous structure of the porous carbon and maintain good stability and crystal structure. The sintering time is set to 7h-12h to allow the raw materials to fully react and ensure the preparation efficiency.
[0088] In a second aspect, an embodiment of the present application provides a lithium iron manganese phosphate material, which is obtained by the preparation method of the lithium iron manganese phosphate material as described above.
[0089] The lithium iron manganese phosphate material provided in the embodiment of the present application has all the advantages of the preparation method of the lithium iron manganese phosphate material, which will not be repeated here.
[0090] like Figure 1 As shown, in the lithium iron manganese phosphate material provided in the embodiment of the present application, the lithium iron manganese phosphate is adsorbed in the porous structure of the porous carbon. The porous carbon can serve as a carrier of the lithium iron manganese phosphate and also help to form a three-dimensional conductive network, thereby improving the conductive properties of the lithium iron manganese phosphate material.
[0091] In a third aspect, an embodiment of the present application provides a battery comprising the lithium manganese iron phosphate material as described above.
[0092] The battery provided in the embodiment of the present application has all the advantages of the preparation method of lithium manganese iron phosphate material, which will not be repeated here.
[0093] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.
[0094] Example 1
[0095] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in a molar ratio of 1.03:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 minutes to obtain a first mixed solution;
[0096] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and then ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0097] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0098] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0099] Example 2
[0100] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in 200 mL of deionized water at a molar ratio of 1.01:0.5:0.5:1, and stirring for 30 minutes to obtain a first mixed solution;
[0101] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0102] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0103] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0104] Example 3
[0105] (1) dissolving lithium acetate, ferric acetate, manganese acetate and diammonium phosphate in a molar ratio of 1.05:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 min to obtain a first mixed solution;
[0106] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0107] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0108] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0109] Example 4
[0110] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in 200 mL of deionized water at a molar ratio of 1.03:0.6:0.4:1, and stirring for 30 minutes to obtain a first mixed solution;
[0111] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0112] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0113] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0114] Example 5
[0115] (1) dissolving lithium acetate, ferric acetate, manganese acetate and diammonium phosphate in 200 mL of deionized water at a molar ratio of 1.03:x:(1-x):1, and stirring for 30 minutes to obtain a first mixed solution;
[0116] (2) adding porous carbon to the first mixed solution, stirring for 30 minutes, and ultrasonically treating for 60 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0117] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -20°C for 5 hours, and then grinding it into powder to obtain a first precursor;
[0118] (4) Under a nitrogen atmosphere, the first precursor is sintered at 650° C. for 7 h to obtain a lithium manganese iron phosphate material.
[0119] Example 6
[0120] (1) dissolving lithium acetate, ferric acetate, manganese acetate and diammonium phosphate in 200 mL of deionized water at a molar ratio of 1.03:x:(1-x):1, and stirring for 30 minutes to obtain a first mixed solution;
[0121] (2) adding porous carbon to the first mixed solution, stirring for 60 minutes, and ultrasonically treating for 30 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000;
[0122] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -50°C for 8 hours, and then grinding it into powder to obtain a first precursor;
[0123] (4) Under a nitrogen atmosphere, the first precursor is sintered at 900° C. for 12 hours to obtain a lithium manganese iron phosphate material.
[0124] Example 7
[0125] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in a molar ratio of 1.03:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 minutes to obtain a first mixed solution;
[0126] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and then ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 1:1000;
[0127] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0128] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0129] Example 8
[0130] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in a molar ratio of 1.03:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 minutes to obtain a first mixed solution;
[0131] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, and then ultrasonically treating for 45 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 10:1000;
[0132] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0133] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0134] Example 9
[0135] The difference between this embodiment and embodiment 1 is that the preparation method of porous carbon is as follows:
[0136] (1) Cut the ginkgo leaves into small pieces, then ultrasonically clean them in deionized water for 30 min, and dry them at 80° C. for 3 h to obtain pretreated leaves;
[0137] (2) placing the pretreated leaves in a tube furnace, sintering at 550° C. for 3 h, cooling, and grinding into powder to obtain a second precursor;
[0138] (3) mixing the second precursor, lithium hydroxide and deionized water in a ratio of 1:5:16, ultrasonically cleaning for 30 min, and then placing in an oven and drying at 80° C. for 6 h to obtain a third precursor;
[0139] (4) The third precursor is placed in a tubular furnace and sintered at 850° C. for 3 h. After cooling, the precursor is ball-milled in a ball mill at a rotation speed of 350 rpm for 2 h to obtain porous carbon.
[0140] Example 10
[0141] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in a molar ratio of 1.03:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 minutes to obtain a first mixed solution;
[0142] (2) adding porous carbon to the first mixed solution, stirring for 45 minutes, ultrasonically treating for 45 minutes, and then adding glucose and stirring for 20 minutes to obtain a second mixed solution; wherein the mass ratio of porous carbon to manganese acetate is 5:1000, and the mass ratio of glucose to manganese acetate is 5:100;
[0143] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0144] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0145] Comparative Example 1
[0146] (1) dissolving lithium acetate, ferric acetate, manganese acetate and ammonium dihydrogen phosphate in a molar ratio of 1.03:0.5:0.5:1 in 200 mL of deionized water, stirring for 30 minutes to obtain a first mixed solution;
[0147] (2) adding glucose to the first mixed solution and stirring for 20 minutes to obtain a second mixed solution; wherein the mass ratio of glucose to manganese acetate is 5:100;
[0148] (3) placing the second mixed solution in a freeze dryer, freeze drying it at -35°C for 7 hours, and then grinding it into powder to obtain a first precursor;
[0149] (4) Under a nitrogen atmosphere, the first precursor was sintered at 750° C. for 9 hours to obtain a lithium manganese iron phosphate material.
[0150] The performance of the lithium iron manganese phosphate material obtained in Example 10 and the lithium iron manganese phosphate material obtained in Comparative Example 1 were tested. The synthesized lithium iron manganese phosphate material, acetylene black and NMP solution containing PVDF (0.02 g mL-1) were thoroughly mixed in a ratio of 8:1:1. The mixed slurry was coated on an aluminum foil and dried at 80°C for 10 hours. The aluminum foil coated with the slurry was then cut into circular electrode sheets with a diameter of 14 mm. After being pressed into a mold (6 MPa), they were placed in a vacuum oven at 120°C and dried for 12 hours. A 2025 type button battery was assembled using a metal lithium sheet as the negative electrode, a diaphragm, an electrolyte, and nickel foam as fillers. Charge and discharge tests were performed at different rates in the voltage range of 2.5-4.2V. The results are as follows Figure 2 As shown: Implementation 10 has excellent rate discharge performance compared to Comparative Example 1. At the same time, the powder resistivity of the lithium iron manganese phosphate materials obtained in Implementation 10 and Comparative Example 1 is tested. The resistivity of Implementation 10 is 21.6Ω*cm, and the resistivity of Comparative Example 1 is 67.4Ω*cm, indicating that the three-dimensional conductive network formed in Implementation 10 greatly improves the conductivity of the lithium iron manganese phosphate material and improves the rate performance of the material.
[0151] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing lithium manganese iron phosphate material, characterized in that: include: Providing a mixed solution, the mixed solution comprising a lithium source, an iron source, a manganese source, a phosphorus source, porous carbon and a solvent; Drying and crushing the mixed solution to obtain a first precursor; Under a protective atmosphere, the first precursor is subjected to a first sintering to obtain a lithium manganese iron phosphate material.
2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In the mixed solution, the molar ratio of lithium, iron, manganese and phosphorus is (1.01-1.05):x:(1-x):1; wherein 0<x<1.
3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The lithium source includes lithium acetate; and / or, the iron source comprises ferric acetate; and / or, the manganese source comprises manganese acetate; And / or, the phosphorus source comprises diammonium phosphate.
4. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The solid content of the mixed solution is 1%-10%.
5. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The mass ratio of the porous carbon to the manganese source is (1-10):1000.
6. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The method for preparing the porous carbon comprises: Provide leaves; The leaves are crushed, cleaned and dried to obtain pre-treated leaves; The pretreated leaves are subjected to a second sintering and then ground into powder to obtain a second precursor; adding the second precursor into an alkaline solution for ultrasonic treatment, and then drying to obtain a third precursor; The third precursor is subjected to a third sintering and then ground to obtain the porous carbon.
7. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: The second sintering of the pretreated leaves comprises: The pretreated leaves are sintered at a temperature of 500° C.-600° C. for 1 h-3 h.
8. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: The second precursor is added into an alkaline solution for ultrasonic treatment, comprising: The second precursor, alkaline reagent and water are mixed in a mass ratio of 1:(3-8):16, and ultrasonically treated for 20-40 minutes; wherein the alkaline reagent includes at least one of lithium hydroxide and potassium hydroxide.
9. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: The step of performing a third sintering on the third precursor comprises: The third precursor is sintered at 800° C.-900° C. for 2 h-4 h.
10. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 9, characterized in that: The mixed solution also includes a carbon source.
11. The method for preparing lithium iron manganese phosphate material according to claim 10, characterized in that: The carbon source includes glucose; And / or, the mass ratio of the carbon source to the manganese source is (1-10):
100.
12. The method for preparing the lithium manganese iron phosphate material according to any one of claims 1 to 9, characterized in that: The step of drying and pulverizing the mixed solution comprises: The mixed solution is freeze-dried at a temperature of -20°C to -50°C for 5h-8h, and then ground into powder.
13. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 9, characterized in that: The first sintering of the first precursor comprises: The first precursor is sintered at a temperature of 650° C.-900° C. for 7 h-12 h.
14. A lithium manganese iron phosphate material, characterized in that: The material is obtained by the preparation method of the lithium manganese iron phosphate material according to any one of claims 1 to 13.
15. A battery, characterized in that: Comprising the lithium manganese iron phosphate material as described in claim 14.
Citation Information
Patent Citations
Porous carbon-based material originated from leaves and preparation method thereof
CN107055504A
Embedded lithium ferric manganese phosphate positive electrode material and preparation method thereof, lithium ion battery and electric equipment
CN114497540A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN118419887A
Cited By
Positive electrode material and preparation method thereof, pole piece and secondary battery
CN120413625A